Effect of the stoichiometry in La0.7(SrxCa0.3-x)MnO3 by x-ray photoelectron spectroscopy for hyperthermia applications - Rivera-Rios, L; Mani Gonzalez, Pierre Giovanni; Farias, Rurik; Elizalde Galindo, Jose Trinidad; CARRILLO FLORES, DIANA MARÍA; Martínez-Guerra, E; Snelgrove, M; Hernandez-Marquez, JA; Cortez-Valadez, M (2020)
The use of physical properties in magnetic materials is a research area aiming to help overcome the biomaterial problems encountered in hyperthermia cancer treatment. A1-xBxMnO3 nanoparticle structures are one such magnetic material which offers functionality in hyperthermia applications. Co-precipitation was employed as a method of nanoparticle synthesis. This process is a low energy method of obtaining nanoparticles, when compared with the traditional ceramic method. The structure and stoichiometry of lanthanum manganite nanoparticles doped with strontium and calcium (LMSCNPs) were obtained by scanning electron microscopy and x-ray photoelectron spectroscopy respectievtly. Mn and La ratios were kept constant during the synthesis. Stoichiometric ratios were varied from x = 0.0 to x = 0.2 for strontium concentration in La0.7Ca0.3-xSrxMnO3. Ca 2p and Sr 3s spectra suggests strontium incorporation increases when the calcium signal decreases. The strontium atoms have a direct effect on the magnetic properties for reordering magnetic domains according to vibrating sample magnetometer results reported previously. The composition between Sr and Ca atoms needs to be around x = 0.15 (rhombohedral) for the effective Curie temperature (Tc) control of LMSCNPs. Tc decreases when the strontium atoms increases, with the results showing that LMSCNPs with a rhombohedral structure have the potential to contribute to hyperthermia treatment.